The Effect of Arm Muscle Strength and Leg Power on Smash Accuracy - Santi Nurohmah; Entan Saptani; Dinar Dinangsit (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This study uses a descriptive correlational method, because it can determine the relationship between 2 or more variables using a spearman correlation research design that aims to determine the relationship between 2 independent variables and 1 dependent variable. The independent variables are arm muscle strength, power leg, while the dependent variable is smash accuracy. The sample of this study were 20 students of elementary school Pakemitan II who were selected using purposive sampling technique. Based on the results of the research obtained push up results of 0.000, vertical jump results of 0.007 and smash results of 0.082 so the conclusion of this normality test is that the data is normal because the residual count is more than 0.05 with a push up test of 0.000> 0.05, vertical jump test results 0.007> and smash test 0.082> 0.05 so the data is normally distributed.  Based on the results of the study it can be concluded that there is no significant relationship. Based on the sig. (tailed) value on push ups which is 0.542> 0.05 and on the vertical jump of 0.900> 0.05, it concludes that there is no significant relationship. when viewed from the guidelines for the degree of relationship based on the pearson correlation value on push ups classified as a very weak correlation category to smash and if the vertical jump is included in the category of very weak correlation to smash.